To Catch A Sex Thief: The Burden of Performance in Rape and Sexual Assault Trials - Rayburn, Corey (Columbia Journal of Gender and Law, 2006)
Jacques’ observation in Shakespeare’s As You Like It describes the typical rape and sexual assault trial in the United States. The complainant plays many different characters throughout the course of the trial. Pre-written cultural scripts dictate her lines. The setting is both the courtroom and the scene of the alleged rape as imagined by the jury. Unique to a rape “play,” however, an accuser cannot be sure which role the jury will assign to her by the time it begins its deliberations. Is she to be cast as a whore? A vengeful liar? A tease? Mentally unstable? If she has the “proper” background and the defendant is a stranger, can she play the role of an innocent Madonna whose perceived purity may result in the rarest of events: a guilty verdict? While every trial has elements of theater, rape and sexual assault cases are unique because they emphasize the gender performances of the accuser and the accused. Complainants who testify are not just recounting the events of the alleged rape. They are also defining the essential parts of their gender roles for the jury. Every statement, mannerism, action, and emotion of the accuser on the witness stand relays information about her gender to the jury. If the jurors deem a performance too emotional, they may assume the accuser is stereotypically hysterical and unreliable. If, however, she appears cold and calculating, the jury may believe she is a “gold-digger” using the criminal trial as a prequel to a lucrative civil suit. If she shows too much anger (as though it were possible for someone who has been raped to be “too angry”), the jury may see vengeance as her motive for “crying rape.” Which predefined gender roles the jury assigns the accuser and accused during the trial are important in determining whose story the jury will ultimately believe.